2020
DOI: 10.1101/2020.07.17.20155986
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The association between ABO blood group and SARS-CoV-2 infection: a meta-analysis

Abstract: At present, existing evidence about the association between SARS-CoV-2 infection and ABO blood group polymorphism is preliminary and controversial. In this meta-analysis we investigate this association and determine SARS-CoV-2 positive individuals odds of having a specific blood group compared to controls. We performed a systematic search on MEDLINE and LitCovid databases for studies published through July 12, 2020. 7 studies met inclusion criteria for meta-analysis, including a total of 13 subgroups of popula… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 29 publications
4
48
1
1
Order By: Relevance
“…A relationship appears to exist between an individual’s ABO blood type and the possibility of contracting a SARS-CoV-2 infection following exposure. Type A blood donors showed the highest frequency of anti–SARS-CoV-2 IgG antibodies, which agreed with the results of a recent meta-analysis showing that SARS-CoV-2–positive individuals were more likely to have type A blood than the other blood types ( Golinelli et al, 2020 ). Another study performed by Guillon et al reported that a monoclonal anti–A antibody or a natural plasma-derived anti–A antibody was able to definitely inhibit the SARS-CoV-2 S protein/ACE2-dependent adhesion to ACE2-expressing cell lines ( Guillon et al, 2008 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A relationship appears to exist between an individual’s ABO blood type and the possibility of contracting a SARS-CoV-2 infection following exposure. Type A blood donors showed the highest frequency of anti–SARS-CoV-2 IgG antibodies, which agreed with the results of a recent meta-analysis showing that SARS-CoV-2–positive individuals were more likely to have type A blood than the other blood types ( Golinelli et al, 2020 ). Another study performed by Guillon et al reported that a monoclonal anti–A antibody or a natural plasma-derived anti–A antibody was able to definitely inhibit the SARS-CoV-2 S protein/ACE2-dependent adhesion to ACE2-expressing cell lines ( Guillon et al, 2008 ).…”
Section: Discussionsupporting
confidence: 90%
“…Another study performed by Guillon et al reported that a monoclonal anti–A antibody or a natural plasma-derived anti–A antibody was able to definitely inhibit the SARS-CoV-2 S protein/ACE2-dependent adhesion to ACE2-expressing cell lines ( Guillon et al, 2008 ). Consequently, the ABO polymorphism might have considerable impact on SARS-CoV-2 susceptibility, linking a number of infected individuals and increasing the relevance of kinetic studies performed during the SARS outbreak in 2002 to 2003 ( Golinelli et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that COVID-19 occurs more in males [ 153 , 154 ], the elderly, and non-O blood type individuals [ 155 , 156 ]. The inflammatory responses and cytokine storm induced by SARS-CoV-2 are extremely variable [ 157 ], and prognosis is conditioned by the host response more than by the infection, since pre-existing comorbidities such as obesity, cardiovascular diseases, arterial hypertension, type 2 diabetes mellitus, and immunosuppression strongly contribute to fatal outcomes [ 158 , 159 , 160 , 161 , 162 ].…”
Section: Development and Perspectives For Italian Public Health Gementioning
confidence: 99%
“…Also the ABO blood group-related susceptibility to various types of viral infections, including HIV, hepatitis B, dengue and influenza viruses, has been consistently reported by several investigators over the last 20 years [5]. This issue has recently gained a renewed interest thanks to the first observations on the association between ABO blood type and Coronavirus Disease 2019 (COVID-19) from China, where the infection began and quickly spread around the world [6]. In particular, it has been hypothesized that individuals belonging to O blood type are less susceptible to Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection than those belonging to non-O blood groups or that have a milder disease [7].…”
mentioning
confidence: 92%